2017
DOI: 10.1634/theoncologist.2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Daratumumab Monotherapy and Pomalidomide Plus Low-Dose Dexamethasone in the Treatment of Multiple Myeloma: A Matching Adjusted Indirect Comparison

Abstract: This matching adjusted indirect comparison of clinical trial data from four studies analyzes the survival outcomes of patients with heavily pretreated, relapsed/refractory multiple myeloma who received either daratumumab monotherapy or pomalidomide plus low-dose dexamethasone. Using this method, daratumumab conferred a significant overall survival benefit compared with pomalidomide plus low-dose dexamethasone. In the absence of head-to-head trials, these indirect comparisons provide useful insights to clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…MAIC analyses have been conducted for biologics across a variety of therapeutic areas, including haemophilia [ 18 ], psoriasis [ 19 ] and multiple myeloma [ 20 ]. The objective of this study was to perform a MAIC of benralizumab versus IL-5-directed monoclonal antibodies for the treatment of patients with severe, uncontrolled asthma and with an eosinophilic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…MAIC analyses have been conducted for biologics across a variety of therapeutic areas, including haemophilia [ 18 ], psoriasis [ 19 ] and multiple myeloma [ 20 ]. The objective of this study was to perform a MAIC of benralizumab versus IL-5-directed monoclonal antibodies for the treatment of patients with severe, uncontrolled asthma and with an eosinophilic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Also, indirect treatment comparison studies of daratumumab monotherapy (pooled from the GEN501 and SIRIUS studies) and comparator therapies (different retrospective cohort studies) have indicated a consistent OS benefit for daratumumab monotherapy. 4,[19][20][21][22][23][24] Adjusted comparisons of patient-level data pooled from daratumumab monotherapy clinical studies (patients treated with 16 mg/kg in the SIRIUS/GEN501 studies) with standard care realworld data from the Czech Republic, 21 United States, 22 International Myeloma Foundation, 23 and International Myeloma Working Group 24 historical control cohorts of patients with RRMM revealed improved OS for daratumumab compared with the realworld historical control data (adjusted hazard ratio for OS, 0.35, 0.30, 0.41, and 0.44, respectively) in heavily pretreated patients with RRMM. Data from the Czech registry revealed that the control cohort differed in median age (64 vs. 62 years), median number of previous therapy lines (5 vs. 4), previous exposure to carfilzomib (41.2% vs. 0.3%) and pomalidomide (55.4% vs. 0.6%), triple or more refractory status (64.2% vs. 5.3%), and OS (11.9 vs. 20.1 months) from daratumumab trial patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MAIC methodology has been applied extensively in oncology to assess the effects of treatments for various tumor types. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%